(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This article shows the results of the observations about Bombus Latr. and Psithyrus Lep. species led from 1997 to 2000 in a tipica! submontain environment of Molise region. Thirteen species have been found, six of which are new records for the region. Concerning B. terrestris, lapidarius, pascuorum, pratorum and humilis, the most abundant and constant species, it has been possible to describe the profiles of the colonies cycles. The observations on the flora visited by the bumble bees have allowed to compile a list of plants with their degree of actractivity and their importance as regards to the different species of bumble bees.